Characterization of a thin-film metal-coated fiber optical phase modulator based on thermal effect with a nonlinear control interferometer - Nunes, Gabriel F.S.; Palma, Vinicius B.; Martin, Roberta I. [UNESP]; Felao, Luiz H.V. [UNESP]; Teixeira, Marcelo C.M. [UNESP]; Kitano, Claudio [UNESP]; Cazo, Rogerio M.; Sakamoto, Joao M.S. (Optica Publishing Group, 2021)
In this work, an optical fiber was coated by a thin-film metal layer to work as a fiber optical phase modulator based on thermal effect. This device was assembled in one of the arms of an all-fiber Michelson interferometer stabilized by a nonlinear control system based on variable structure and sliding modes. The frequency response reached 200 Hz, which can be considered high for a device based on the thermal effect. Compared with a fiber optical phase modulator based on the piezoelectric effect, the thermal modulator presented a higher scale factor per meter of optical fiber, showing the potential to work as a simple, low-cost, small-sized, short length, lightweight, and low-voltage fiber optical phase modulator.